Comparison of three types of redox active polymer for two photon stereolithography. (24th January 2017) - Folkertsma, Laura; Zhang, Kaihuan; Hempenius, Mark A.; Vancso, G. Julius; van den Berg, Albert; Odijk, Mathieu
Abstract : Three‐dimensional printing and stereolithography of functional materials for nanofabrication have recently generated a big amount of interest, as have responsive materials. We have investigated the applicability of the redox‐responsive polymer poly(ferrocenylsilane) (PFS) for stereolithography purposes. Three types of PFS were synthesized, each functionalized with specific properties to make them interesting for use in nanofabrication. These properties include various stiffness, crosslink densities and hydrophobicities. One of the three PFSs is polycationic, therefore resulting in a hydrogel structure. We show structures fabricated from these materials. Common challenges in using new materials such as these for two‐photon stereolithography are discussed. © 2017 The Authors Polymers for Advanced Technologies Published by John Wiley & Sons Ltd